Partial interference elimination based retrospective interference alignment scheme in the downlink MIMO broadcast channel - Jingfu LI; Wenjiang FENG; Wenshou WANG; Weiheng JIANG; Chonghai YANG (Tongxin xuebao)
For interference networks, the degree of delay (DoD) was proposed to quantify the information delay among traditional interference alignment (IA) schemes.It indicated that networks suffer from the issue of latency caused by IA schemes.Herein, for the MIMO downlink broadcast channel (BC), the partial interference elimination based retrospective interference alignment scheme (PIE-RIA) was put forward.In the scheme, relay technique was adopted to eliminate partial interference signals so that part of desired symbols could be decoded promptly in user sides.Meanwhile, in the last slot, the eliminated signals could be regenerated in base station side with the retrospective interference alignment (RIA) scheme .The simulation results show that PIE-RIA scheme maintains degree of freedom (DoF) gain of RIA scheme and in the meantime, achieves lower DoD than the other schemes.